2013
DOI: 10.3402/ejpt.v4i0.20124
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing forward of young refugees: a perspective on resilience research directions

Abstract: While studies on the consequences of trauma and forced migration on young refugees have focused mainly on their pathology, a focus on resilience in young refugees is needed to adequately represent their response to adversity and to help understand their needs. The aim of this article is to present a proposed study of resilience in young refugees which has been informed by an overview of achievements and challenges in the field of resilience.In order to advance the field of resilience, several topics need clari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 81 publications
3
58
0
3
Order By: Relevance
“…It may also be a nature of the sample selection itself, which was highly trauma exposed, and approximately half of the sample had sought mental health treatment in the past. This finding is, however,consistent with one perspective of resilience that encompasses the possibility that individuals can be resilient and yet still be suffering from negative outcomes of the trauma (Sleijpen et al, 2013; Southwick et al, 2014). These findings also align well with the systems perspective that would expect variability in resilient responses, as a function of outcome of interest, context, and impact of other systems (e.g.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…It may also be a nature of the sample selection itself, which was highly trauma exposed, and approximately half of the sample had sought mental health treatment in the past. This finding is, however,consistent with one perspective of resilience that encompasses the possibility that individuals can be resilient and yet still be suffering from negative outcomes of the trauma (Sleijpen et al, 2013; Southwick et al, 2014). These findings also align well with the systems perspective that would expect variability in resilient responses, as a function of outcome of interest, context, and impact of other systems (e.g.…”
Section: Discussionsupporting
confidence: 83%
“…These conflicting findings may be consistent with another line of research suggesting that resilience is not necessarily the most common outcome, particularly following certain stressors (e.g. severe interpersonal traumas; Steenkamp, Dickstein, Salters-Pedneault, Hofmann, & Litz, 2012) or in certain populations, such as refugees (Sleijpen et al, 2013). Here, it has been suggested that it may be inappropriate to consider mental health problems as evidence of lack of resilience, with the presence of some psychological symptoms considered to be a normative reaction to extreme experiences or circumstances (Papadopoulos, 1999; Sleijpen et al, 2013; Southwick, Bonanno, Masten, Panter-Brick, & Yehuda, 2014).…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations